Evaluation of microbial content of some sunscreen creams in Iran’s market - Narges Sedghi Sharif-Abad; Majid Saeedi; Reza Enayatifard; Katayoun Morteza-Semnani; Jafar Akbari (Pharmaceutical and Biomedical Research, 2015)
The risk of microbial contamination in the cosmetic products especially in smuggled preparations and transmission of it to consumers is very high. In this study, the microbial content and the pollution of some sunscreen creams in the market and one sample in official market as witness were evaluated. The microbial content (bacterial total count, fungal count, and presence of Pseudomon asaeroginosa, Staphylococcus aureus and Entrobacter) of 5 samples of sunscreen cream in the market and two samples in official market were evaluated by two methods (pour plate and Multiple tube technique). All samples showed high microbial and fungal contamination. Entrobacters was observed in all samples. Staphylococcus aureus was recognized in one of the non-standard sunscreens. High level of contamination in sunscreen creams, can affect consumers, health. It seems that low grade raw materials, and insufficient manufacturing surveillance in production process are the main factors in the contamination.